Joint statement of the German Radiological Society and the German Respiratory Society on a quality-assured early detection program for lung cancer with low-dose CT: Positionspapier der Deutschen Röntgengesellschaft und der Deutschen Gesellschaft für Pneumologie und Beatmungsmedizin zu einem qualitätsgesicherten Früherkennungsprogramm des Lungenkarzinoms mittels Niedrigdosis-CT - Wormanns, Dag; Kauczor, Hans-Ulrich; Antoch, Gerald; Biederer, Jürgen; Herth, Felix; Vogel-Claussen, Jens; Reinmuth, Niels; Pfeifer, Michael (RöFo. Supplement, 2019)
Substantial new data on the early detection of lung cancer with low-dose CT has become available since the last joint statement of the German Radiological Society and the German Respiratory Society was published in 2011. The German S3 guideline on lung cancer was revised in 2018 and now contains a weak recommendation regarding the early detection of lung cancer with low-dose CT in a quality-assured early detection program. These new developments required a change in the position of the involved professional societies. This joint statement describes the main features of a qualityassured program for the early detection of lung cancer with low-dose CT in Germany.
Gesehen am 15.04.2020